2022
DOI: 10.1039/d2se00520d
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Co-based metal organic framework nanostructures for excellent potassium- and lithium-ion storage: kinetics and mechanism studies

Abstract: Thanks to the low cost and earth's abundant potassium resources, potassium ion batteries (PIBs) have attracted much interest as alternative energy storage devices. However, there is still a great challenge...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 79 publications
(143 reference statements)
1
8
0
Order By: Relevance
“…[ 30–33 ] Unfortunately, its low packing density leads to a low volume specific energy density of nanomaterials, limiting the practical application. [ 33–36 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 30–33 ] Unfortunately, its low packing density leads to a low volume specific energy density of nanomaterials, limiting the practical application. [ 33–36 ]…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33] Unfortunately, its low packing density leads to a low volume specific energy density of nanomaterials, limiting the practical application. [33][34][35][36] In contrast to the rapid advances mentioned above in the different methods to enhance the direct-viewing performance of TiNb 2 O 7 , its underlying lattice expansion characteristics during cyclic charge/discharge process, however, seem to be largely overlooked. Unlike zero-strain Li 4 Ti 5 O 12 , the expansion/construction of lattice volume during the cyclic charge/discharge process deserves attention.…”
Section: Introductionmentioning
confidence: 99%
“…The coordination reaction between metal nodes and organic ligands results in a porous network structure and endows MOFs with a large specific surface area, which is conducive to material contact, transport and exchange and ensures the continuation of chemical reactions. [145][146][147] The abundant pores, diverse crystal structures, and outstanding redox activity in MOFs make them widely applicable for energy conversion. 148 In particular, the application of MOFs and their derivatives in bifunctional catalysts (OER/ORR) and their extension (metal-air batteries) provides a natural advantage (Fig.…”
Section: Metal-organic Framework and Their Derivativesmentioning
confidence: 99%
“…In the former case, Cu is reduced from Cu II to Cu I , while in the latter Co II does not change its oxidation state. [26][27][28] Thus, in principle, metal oxidation reduces the faradaic capacity of Ni 3 (HHTP) 2 compared to those of other triphenylene-based MOFs. In particular, the study of the Co 2 (HHTP) 3 MOF 26 reported a capacity of 332 mA h g −1 at 0.1 A g −1 vs. the value of 631 mA h g −1 at 0.2 A g −1 for Cu 2 (HHTP) 3 .…”
Section: Papermentioning
confidence: 99%
“…The CV plots and XPS spectra before and after cycling reveal the oxidation of Ni from +II to +III during Li + intercalation while the negative charges are accumulated in the HHTP moieties. Despite the similarity of Ni 3 (HHTP) 2 with analogous MOFs, such as Co 3 (HHTP) 2 26 and Cu 3 (HHTP) 2 , 27,28 the metal node exhibits different redox behavior during lithiation processes. Finally, galvanostatic plating-stripping cycles are performed using as working electrodes bare copper and copper covered with Ni 3 (HHTP) 2 .…”
Section: Introductionmentioning
confidence: 99%